1979
DOI: 10.1111/j.1095-8312.1979.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizidine alkaloids in arctiid moths (Lep.) with a discussion on host plant relationships and the role of these secondary plant substances in the Arctiidae

Abstract: Pyrrolizidine alkaloids (PA) have been identified in six species of Arctiidae reared on Senecio and Crotalaria. These include senecionine, seneciphylline, integerrimine, jacobine, jacozine, jacoline, jaconine and a metabolite (C,,H,,NO,) from Senecio, and monocrotaline, trichodesmine and crispatine from Crotalaria.The all-red aberration of Tyriajacobaeae (var. conyij contained much less of the metabolite than normal examples of this species. Female Spilosoma lutea reared on the same plants of S. Jhcobaea cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…PAs are known to deter generalist insect herbivores (Bentley et al, 1984;Dreyer et al, 1985;van Dam et al, 1995;Hägele and Rowell-Rahier, 2000). Specialist herbivores can detoxify (Hartmann, 1999;Naumann et al, 2002) and sequester PAs (Rothschild et al, 1979;Dobler, 2001;Pasteels et al, 2003). Larval performance of the specialist moth Tyria jacobaeae L. was not affected by different PA profiles in its host plant S. jacobaea (Macel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…PAs are known to deter generalist insect herbivores (Bentley et al, 1984;Dreyer et al, 1985;van Dam et al, 1995;Hägele and Rowell-Rahier, 2000). Specialist herbivores can detoxify (Hartmann, 1999;Naumann et al, 2002) and sequester PAs (Rothschild et al, 1979;Dobler, 2001;Pasteels et al, 2003). Larval performance of the specialist moth Tyria jacobaeae L. was not affected by different PA profiles in its host plant S. jacobaea (Macel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These butterflies apply from their proboscides a fluid capable of dissolving alkaloids and then re-imbibe it. Both sexes of these butterflies store alkaloids apparently for defense (Edgar et al 1976;1979;Rothschild et al 1979;Conner et al 1981). Owen (1971) reported that danaine butterflies use withered and damaged plants and floral nectar as sources of alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of arctiid moths for example, sequester PAs as larvae and transfer them through the pupa to the adult stage (Boppré 1990;Hartmann & Witte 1995). Well studied species include the moths Utetheisa ornatrix (Eisner 1980;Eisner & Meinwald 1987) and Tyria jacobaeae (Aplin et al 1968;Ehmke et al 1990;Rothschild et al 1979). Some butterflies in contrast take up PAs only in the adult stage.…”
Section: Discussionmentioning
confidence: 99%